From farm-workers to farm-owners: a case study of the socio-economic impact of a land reform project on Battlesden farm, Alice, Eastern Cape - Nyanda, Langaliphumile (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This is an evaluation of a land reform project of a community which was given land in 2001. There were 16 participants who were interviewed to give their perspectives on different areas of the project which, including the functioning of the Communal Property Associations (CPA), the role of strategic partners such as agribusinesses, and the support provided by the state in ensuring the success of the project. The participants were also asked about the general development of the farm since ownership was transferred to the community in 2001. The study revealed disappointing results in the state of the farm, and the lack of development that has taken place. This was evident in the functioning of the CPA, and the high unemployment which was prevalent on the farm. There were elements of dependency which resulted from the mentorship of the agribusiness, as well as a lack of state support in the general operations of the farm.
Keywords: Battlesden Farm (South Africa); Farmers -- Social conditions -- South Africa -- Eastern Cape -- Case studies; Agricultural laborers -- Social conditions -- South Africa -- Eastern Cape -- Case studies; Land tenure -- Government policy -- South Africa; Land reform -- South Africa -- Case studies; Rural development -- Sociological aspects -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape -- Case studies